Kelayakan Strategi Korporasi Universitas Argopuro Jember Dalam Persaingan Industri Pendidikan Tinggi Pada Era “Distance Learning” Pasca Pandemi Covid-19 - Utami, Riza Wahyu; Sayidah, Nur; Ady, Sri Utami (Majalah Ilmiah DIAN ILMU, 2023)
The aim of presenting a scientific paper from the author is to test thefeasibility of implementing the Argopuro University (UNIPAR) Jember corporate strategy in the distance learning era as an implementation of the newcultural normal after Covid-19. As a research data sample, it was obtained from58 UNIPAR employees as respondents by filling in questionnaires distributed bythe author, and then regression analysis was carried out on the data aftercarrying out data validity-reliability, suitability and correlation betweenvariables. Measuring the feasibility of corporate strategy is carried out byassessing employees' understanding and application of the vision, mission andcorporate culture which is linked to the results of comparing performanceachievements between before and after the implementation of distance learning(post the Covid-19 pandemic) at UNIPAR Jember.The results of the analysis and testing showed that employees'understanding and implementation of the vision, mission and corporate cultureat work were in the very good category, and there were differences inperformance achievements between before and after implementing the distancelearning system (before/after the new cultural normalcy after the Covid-19pandemic ) and the results of implementing corporate strategy have a positiveand significant relationship to employee productivity and contributionachievements, and also have a tendency to reduce employee performance atPGRI Argopuro Jember University post-Covid-19 Pandemic (sig value = 0.0029< 0.05; Correlation (R ) = 0.376, output (R) = 0.239) which can be interpretedas meaning that the influence of understanding and implementing corporatestrategy = 23.9% on employee performance achievements, therefore theconclusion obtained is that the decline in employee performance afterimplementing the distance learning system is caused by strategy. The JemberArgopuro University corporation is out of date and it is recommended thatredefinition be carried out.